Quid Pro Quo Sexual Harassment Involving an Employee Through Staycation Modus - Isnawan, Fuadi (Magister Hukum Universitas Semarang, 2025)
Sexual harassment in the workplace remains a persistent problem that undermines human dignity and often arises from power imbalances or gender inequality. Such acts not only degrade and humiliate victims but also negatively affect their physical, psychological, and social well-being. In Indonesia, the Criminal Code (KUHP) provides only limited recognition of sexual violence, leaving many forms of harassment insufficiently regulated. This study aims to analyze criminal law policies in addressing workplace sexual harassment, with particular attention to the scope of criminalization and the effectiveness of legal enforcement. Using a normative legal research method combined with a case study approach, the study examines the legal framework, its application in practice, and its alignment with the public interest. The findings indicate that current criminal law provisions inadequately capture the diversity of sexual harassment forms and that law enforcement tends to be reactive rather than preventive. The study contributes by highlighting the urgency of reforming Indonesia’s criminal law policy to ensure comprehensive protection for victims, accountability for perpetrators, and the integration of preventive measures alongside repressive sanctions. In conclusion, the criminalization of workplace sexual harassment must extend beyond narrow definitions and be grounded in public interest, legal certainty, and victim protection, offering a more holistic approach to justice in the workplace.